A Focus on Selection for Fixation - John Tsotsos; Iuliia Kotseruba; Calden Wloka (Journal of Eye Movement Research)
A computational explanation of how visual attention, interpretation of visual stimuli, and eye movements combine to produce visual behavior, seems elusive. Here, we focus on one component: how selection is accomplished for the next fixation. The popularity of saliency map models drives the inference that this is solved, but we argue otherwise. We provide arguments that a cluster of complementary, conspicuity representations drive selection, modulated by task goals and history, leading to a hybrid process that encompasses early and late attentional selection. This design is also constrained by the architectural characteristics of the visual processing pathways. These elements combine into a new strategy for computing fixation targets and a first simulation of its performance is presented. A sample video of this performance can be found by clicking on the "Supplementary Files" link under the "Article Tools" heading.